Steam synergic effect on oxygen carrier performance and WGS promotion ability of iron-oxides. (15th January 2021) - Chen, Qindong; Hu, Song; Xu, Qiyong; Su, Sheng; Wang, Yi; Xu, Kai; He, Limo; Xiang, Jun
Abstract: During chemical looping process, the presence of H2 O has great effect on oxygen transfer and hydrogen generation process, thus making the reaction become more complicated. In this study, Fe2 O3 was chosen as the original oxygen carrier and its oxygen carrying capacity and reactivity under different H2 O/CO molar ratios were systematically investigated. The chemical compositions of reacted iron-based oxides were measured by Mössbauer spectroscopy. According to Mössbauer spectroscopy results and product gas analysis, the paper gave further insight into the impact of H2 O on oxygen carrying property and catalyzed effect of iron-based oxides. The results indicated that: (i) The oxygen carrying capacity of Fe2 O3 decreased from 45.93% to 11.33% (the theoretical maximum to be 100%) when the H2 O/CO ratio varied from 0:1 to 2:1. (ii) The maximum CO2 conversion rate, which reflects the reduction reactivity, was closely related to H2 O/CO ratio and achieved the maximum (4.83%/min) at a H2 O/CO ratio of 1:1. (iii) The presence of H2 O could promote the reduction process of Fe2 O3 to generate Fe3 O4 . (iv) Both Fe3 O4 and FeO which existed as reduction states of iron oxides had ability to promote the water-gas shift reaction during oxygen transfer process. Highlights: H2 O will decrease the oxygen carrying capacity of Fe2 O3 . H2 O can promote the reduction reaction of Fe2 O3 to Fe3 O4. H2 O will hinder the further reduction of Fe3 O4 and FeO. Both Fe3 O4 and FeO produced during reduction reaction can improve the WGS reaction.